PRESERVATION OF HOT CHILI WITH ACTIVATED NATURAL ZEOLITE - Dewi Fatimah; Lenny M. Estiaty (Institut Teknologi Bandung, 2003)
Investigation has been done for chilli (keriting and hot beauty type) preservation using natural silicate (zeolite). Zeolite from Cikancra (mordenite and clinoptilolite type is prepared in various particle sizes and activated at different temperatures. The activated zeolite is tested for its ability to absorb water. It is found that zeolite with particle size of -100 +140 mesh and activated at 400ºC has the highest capability for water absorption. This zeolite is then used in the preservation tests. Zeolite can extend the preservation of chillies up to 18 days for